2020
DOI: 10.3389/fphys.2020.576150
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Analysis of Small Extracellular Vesicles in Physical Exercise

Abstract: Physical exercise induces acute physiological changes leading to enhanced tissue cross-talk and a liberation of extracellular vesicles (EVs) into the circulation. EVs are cell-derived membranous entities which carry bioactive material, such as proteins and RNA species, and are important mediators of cell-cell-communication. Different types of physical exercise interventions trigger the release of diverse EV subpopulations, which are hypothesized to be involved in physiological adaptation processes leading to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 77 publications
1
21
1
Order By: Relevance
“…Still, currently no isolation method exists, that purifies only one EV subtype free of co-isolated non-EV material (protein aggregates, lipoproteins, etc. ), which is especially important when studying EVs and their cargo and functions in body fluids [ 45 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, currently no isolation method exists, that purifies only one EV subtype free of co-isolated non-EV material (protein aggregates, lipoproteins, etc. ), which is especially important when studying EVs and their cargo and functions in body fluids [ 45 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the analysis of the methylation profile of cfDNA shows that about 32 % of cfDNA is derived from granulocytes, 30 % from erythrocyte progenitors, 23 % from monocytes and lymphocytes, 9 % from endothelial cells, and only 6 % from other cells including neurons and hepatocytes [11], while a sub-characterization for exercise released cfDNA has not been conducted yet. We and others found that next to muscle cells, platelets, endothelial cells, and leukocytes, significantly contribute to the pool of EVs released into plasma following physical exercise (reviewed in [48,6466]). Like for cfDNA, the underlying signaling mechanisms are not fully understood, but an association with shear stress and the activation of coagulative processes are discussed [48].…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that next to muscle cells, platelets, endothelial cells, and leukocytes, significantly contribute to the pool of EVs released into plasma following physical exercise (reviewed in [48,6466]). Like for cfDNA, the underlying signaling mechanisms are not fully understood, but an association with shear stress and the activation of coagulative processes are discussed [48]. Since cfDNA and EVs seem to be released by similar cell types during physical exercise, a joint or related release mechanism is possible, but remains speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to muscle cells, platelets, endothelial cells and leukocytes contribute to the multiple sources of exercise-induced EVs in the blood stream [82][83][84][85]. Accordingly, the circulating mixture of exercise-induced EVs carries a diverse set of cargo proteins, metabolites and miRNAs involved in processes such as angiogenesis, immune signaling and glycolysis, reviewed in [86]. A study in human exercising volunteers confirmed the distinct biological processes [80].…”
Section: Evs In Physical Exercise-tumor Cross-talkmentioning
confidence: 95%